Comparison of Chemical Constituents of Some Plant Species of Lamiaceae Family Grown Conventionally and Organically - Özlen Özkurt; Rifat Battaloğlu (Turkish Journal of Agriculture: Food Science and Technology)
In this study, the chemical constituents of Origanum onites, Salvia officinalis and Lavandula officinalis plants belonging to Lamiaceae family grown by conventional and organic methods were determined by soxhlet extraction. Gas Chromatography-Mass Spectrometry (GC-MS) method was used to determine the chemical constituents of conventionally and organically grown plant samples. When the results of the analyses were examined, out of 97 chemical components of Salvia officinalis plant, 50 components were determined from plants grown with conventional farming methods and 78 components were determined from plants grown with organic farming methods. Of the 38 components detected in Origanum onites, 36 components were determined from plants grown with conventional farming methods and 38 components were determined from plants grown with organic farming methods. Out of 60 components of Lavandula officinalis, 40 components were determined from plants grown with conventional farming methods and 60 components were determined from plants grown with organic farming methods. In terms of chemical structure, the components are divided into different classes as hydrocarbons, monoterpenes, monoterpenoids, sesquiterpenes, sesquiterpenoids, diterpenes, diterpenoids, fatty acids and derivatives, and phenolic compounds.